The Impact of Workplace Environment, Supply Chain Performance and Integration on Work Productivity: Mediating Role of Organizational Culture - Agussalim, M; Yanti, Novi (ExcelingTech, 2020)
The work productivity has played an essential role in the success of the organization and also enhance the economic growth and supply chain practices is considered as the essential element to improve the work productivity and also gain the attention of well-known researchers. Thus, the present study has examined that impact of the workplace environment, supply chain performance and supply chain integration on the work productivity of the banks in Indonesia. The purpose of the ongoing study is also the investigation of mediating impact of organizational culture on the nexus of the workplace environment, supply chain performance, supply chain integration and work productivity of the banks in Indonesia. The employees of the banks that linked with supply chain process are the respondents selected by using simple random sampling and gathered data by using questionnaires. The smart-PLS, an effective tool for data analysis has been employed for analysis purpose. The results highlighted that the workplace environment, supply chain performance and supply chain integration have a positive association with work productivity. The results also indicated that organizational culture positive mediates among the nexus of the workplace environment, supply chain performance, supply chain integration and work productivity of the banks in Indonesia. The outcome provided the guidelines to the regulators that they should enhance their focus on the supply chain practices that could increase the work productivity while leads the organization towards success.